2022
DOI: 10.1002/path.5845
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models predict the primary sites of head and neck squamous cell carcinoma metastases based on DNA methylation

Abstract: In head and neck squamous cell cancers (HNSCs) that present as metastases with an unknown primary (HNSC‐CUPs), the identification of a primary tumor improves therapy options and increases patient survival. However, the currently available diagnostic methods are laborious and do not offer a sufficient detection rate. Predictive machine learning models based on DNA methylation profiles have recently emerged as a promising technique for tumor classification. We applied this technique to HNSC to develop a tool tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…All the foods we eat are genetically modified. From chemical additives, multi-colored harmful plastic containers in the name of modular kitchen, food prepared in the oven, Teflon coating on non-stick dosa to drinking milk, there is a risk of cancer in everything [2]. Beauty face paints, hair dyes, powders, sunscreen lotions...…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…All the foods we eat are genetically modified. From chemical additives, multi-colored harmful plastic containers in the name of modular kitchen, food prepared in the oven, Teflon coating on non-stick dosa to drinking milk, there is a risk of cancer in everything [2]. Beauty face paints, hair dyes, powders, sunscreen lotions...…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cancer treatment doctors say that early stage disease can be completely cured. In the changing chemical world, new diseases are emerging [2]. At the same time, there is no escape from it without awareness, basic clarity and self-defense.…”
Section: Introductionmentioning
confidence: 99%
“…Most publications on similar classi cation tasks reported the successful use of a single RF model with additional calibration methods [35,36]. However, in a comparison of the LOGREG, NN, SVM, and RF models for predicting the primary site of HNSC tumors from their DNA methylation pro le, the RF model performed considerably worse than the other three classi ers [21]. A comparison of a multitude of methods for the characterization and prediction of HPV in patients with OPCs showed that a generalized linear model (with a logistic kernel) performed best among all methods and was substantially better than the RF model [37].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning techniques applied to medical image analysis can integrate qualitative and quantitative imaging features to construct an optimal diagnostic algorithm prediction model with high diagnostic accuracy [20]. Models based on DNA methylation pro les [21] and cancer genome information [22] have been used to predict the origin of cancers of unknown primary. However, experience in the application of ML techniques based on radiomic features from imaging of head and neck cancer is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, machine learning and data mining have contributed to the biomarker screening for early detection, diagnosis, drug application, metastases, and prognosis of various cancers (9)(10)(11). For example, by employing four machine learning models, Leitheiser et al (12) predicted the primary sites of HNSC metastases based on DNA methylation. Rendleman et al (13) developed a machine learning method to improve the usability of the HNSC dataset for enhancing future oncological decisions and clinical applications.…”
Section: Introductionmentioning
confidence: 99%